Digital Leadership as a Resource to Enhance Managers’ Psychological Well-Being in COVID-19 Pandemic Situation in Indonesia - Dewi, Rany Komala; Sjabadhymi, Bertina (UI Scholars Hub, 2021)
Research Aims: The digitalization of work forced by the coronavirus disease (COVID-19) pandemic has led to excessive job demands that might reduce psychological well-being. Hence, this study aims to explore the relationship between digital leadership and psychological well-being during the COVID-19 pandemic situation. Design/Methodology/Approach: A total of 1,899 managers participated in this study. A logistic regression analysis was performed to test for associations between well-being and digital leadership skills. Research Findings: The results show that as a unidimensional variable, digital leadership is a strong predictor of psychological well-being. However, as a multidimensional variable, the digital leadership – skill dimension has significant and positive effects on psychological well-being, whereas the digital leadership – attitude, competences, and behavior dimension does not have a significant effect on psychological well-being. Theoretical Contribution/Originality: As a multidimensional variable, digital leadership has a partial effect in determining psychological well-being. Managerial Implication in the Southeast Asian context: Improving digital leadership does not guarantee that psychological well-being will improve. However, specifically improving the digital leadership – skill dimension will considerably influence the likelihood of having high psychological well-being. Research Limitation & Implications: The slightly low, but still acceptable, Cronbach’s alpha coefficient on the digital leadership – attitudes, competences, and behavior dimension scale may improve on adding more items. Since the study participants were from one organization and one country, future studies could include several organizations and countries to enrich the findings.